2011
DOI: 10.1073/pnas.1019391108
|View full text |Cite
|
Sign up to set email alerts
|

CCCTC-binding factor (CTCF) and cohesin influence the genomic architecture of the Igh locus and antisense transcription in pro-B cells

Abstract: Compaction and looping of the ∼2.5-Mb Igh locus during V(D)J rearrangement is essential to allow all V H genes to be brought in proximity with D H -J H segments to create a diverse antibody repertoire, but the proteins directly responsible for this are unknown. Because CCCTC-binding factor (CTCF) has been demonstrated to be involved in long-range chromosomal interactions, we hypothesized that CTCF may promote the contraction of the Igh locus. ChIP sequencing was performed on pro-B cells, revealing colocalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
272
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(293 citation statements)
references
References 35 publications
16
272
2
Order By: Relevance
“…ChIP experiments for H3K4me2, H3K27ac, and P300 were performed with chromatin from RAG-deficient thymocytes (C57BL/6) as described previously (59). The ChIP DNA was purified using a Qiagen DNA purification kit and subjected to whole genome amplification (Sigma), labeled, and hybridized to custom Nimblegen microarrays according to the manufacturer's protocol by Mogene.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP experiments for H3K4me2, H3K27ac, and P300 were performed with chromatin from RAG-deficient thymocytes (C57BL/6) as described previously (59). The ChIP DNA was purified using a Qiagen DNA purification kit and subjected to whole genome amplification (Sigma), labeled, and hybridized to custom Nimblegen microarrays according to the manufacturer's protocol by Mogene.…”
Section: Methodsmentioning
confidence: 99%
“…Global mapping of CTCF-binding sites and CTCF-associated chromatin loops also suggests that CTCF can facilitate long-distance interactions for coordinated gene expression, demarcate chromatin boundaries, or facilitate enhancer-promoter communication (19-23). However, it remains difficult to predict how CTCF might function at any individual locus.Recently, several studies have suggested a role for CTCF in the regulation of V(D)J recombination at antigen receptor loci (9,(24)(25)(26)(27)(28). For example, knockdown of CTCF in a pro-B-cell line reduced DNA contacts between regulatory elements that flank the D H J H C H region, increased antisense transcription through the D H and V H regions, and partially suppressed contraction of the Igh locus (25).…”
mentioning
confidence: 99%
“…Recently, several studies have suggested a role for CTCF in the regulation of V(D)J recombination at antigen receptor loci (9,(24)(25)(26)(27)(28). For example, knockdown of CTCF in a pro-B-cell line reduced DNA contacts between regulatory elements that flank the D H J H C H region, increased antisense transcription through the D H and V H regions, and partially suppressed contraction of the Igh locus (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution chromatin conformation studies have revealed that cohesin forms long-range interactions between its binding sites (Figure 2) [13-18, [67][68][69][70]. Current models support the idea 6 that cohesin controls gene expression by contributing to the organisation of higher-order chromatin structure.…”
Section: Cohesin Shapes Interphase Chromatin By Forming Long-range Inmentioning
confidence: 95%